ONLINE INTERPRETING LEARNING DURING PANDEMIC FROM STUDENTS’ PERSPECTIVE - Reyna Vidyantari (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2021)
ABSTRACT Studying interpreting is challenging, and even more when done online. This paper studied five students' experiences when underwent an online interpreting course. Data is collected through interviews; this article described some problems that emerged from online interpreting learning in Indonesia. The author found that there were several internal and external factors that caused some problems during online sessions. Although the subjects were satisfied with online learning, all of them prefer to do face-to-face learning. This article was initial research in the online interpreting field. It is expected that there will be further research to find effective strategies for implementing online interpreting learning. Keywords: Online class; interpreting; pandemic; language; learning; students